Ung Uro Unsettling Climates in Nordic Art, Architecture and Design - Halland, Ingrid (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"How can the unsettling climates of our times be understood? How can art, architecture, and design that engages with the complexities of our current age be analysed and criticised? Etymologically, the Norwegian word uro carries a double meaning: it can denote both 'disquiet and unease' as well as 'riot and disturbance'. The word stems from the Old Norse úró and is used to describe political turmoil, social disorder, and a psychological state of restless anxiety. Thus the title of this anthology, Ung Uro (literally 'young unrest'), intimates the paradoxical tension between describing our new geological condition - the Anthropocene - and referring to the reactions this condition provokes. In Ung Uro. Unsettling Climates in Nordic Art, Architecture and Design, thirteen young writers, critics, and art historians examine how Nordic visual art, architecture, and design relate to this new state of unease. Their topics span from early 20th century landscape painting to contemporary bio-acoustics, from Snøhetta's energy-positive architecture to the Sami chant yoik, and from IKEA showrooms to fungi and bees as co-creators of artistic work. The empirical material consists mainly of specific exhibitions, artistic projects, and related events that took place for the most part in Norway from 2018 to 2020, and therefore the book is also a record of critical issues at stake in Nordic contemporary art and culture in the late 2010s. All those with an interest in contemporary art, design, and visual studies, including students, will find this book valuable."